2018
DOI: 10.3892/mco.2018.1687
|View full text |Cite
|
Sign up to set email alerts
|

Primary adrenal teratoma: A case series and review of the literature

Abstract: Primary adrenal teratoma is a rare type of cancer. Of the 338 patients who underwent adrenalectomy during this study, only 2 (aged 69 and 29 years) were diagnosed with adrenal teratoma and underwent laparoscopic retroperitoneal adrenalectomy. For the purposes of the present study, the term 'adrenal teratoma' was searched in the PubMed database, and 237 articles published between June 1952 and March 2017 were retrieved. However, we were only able to identify 10 relevant studies. In total, these studies reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…Only a very few case reports have been documented in literature so far [ 12 ] which make our case unusual. An accurate diagnosis of a teratoma cannot be made on clinical basis [ 2 , 7 ]. Diagnosis can be possible with the help of plain radiography, ultrasound abdomen and computed tomography (CT) or magnetic resonance image (MRI) of abdomen [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only a very few case reports have been documented in literature so far [ 12 ] which make our case unusual. An accurate diagnosis of a teratoma cannot be made on clinical basis [ 2 , 7 ]. Diagnosis can be possible with the help of plain radiography, ultrasound abdomen and computed tomography (CT) or magnetic resonance image (MRI) of abdomen [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound of the abdomen is usually the first imaging modality used in pediatric [ 7 , 8 ]. It can greatly differentiate between cystic and solid elements [ 2 , 12 ]. CT scan and MRI are useful to delineate the extent of the disease in retro-peritoneum and its relationship to major vessels, which provide better preoperative planning and increased likelihood of complete removal of the tumor with less iatrogenic damage [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Liang Zhou et al in a Review of Literature of Primary adrenal teratoma found only 18 adults and 7 paediatric cases. 13 Among Paediatric age group Boys are more common than Girls. Only few cases are reported as Girl child in literature where as our series has two female cases.…”
Section: Discussionmentioning
confidence: 99%